Conceptual and Ontological Modeling of In-Vehicle Life-logging Software Systems - Puchianu, Crenguta M.; Bautu, Elena (Procedia computer science, 2020)
In-vehicle software systems that contain interconnected lifelogging components such as in-vehicle infotainment systems, smartphones, On Board Diagnostics (OBD) devices or wearable devices, operate with very large volumes of data. To manage the complexity and big volume of data, it is necessary to analyze the data and build models. Our goal, in this paper, is to build suitable models for in-vehicle lifelogging data, in the context of vehicle information standardization. To this aim, we build conceptual and ontological models for the data that is transmitted between the lifelogging components of an in-vehicle system, by applying conceptualization and abstraction mechanisms. Conceptual models can be built considering three viewpoints: functional, architectural, and behavioral. In this paper, we constructed a facet of the architectural view that contains the Unified Modeling Language (UML) classes and the relationships between them. Next, we designed and implemented the class diagram and generated each type of message in JavaScript Object Notation (JSON) format. In order to model the data and their semantics, we built an application ontology in Web Ontology Language (OWL). The consistency of this ontology was verified in Protégé. The ontology was further generated in the JavaScript Object Notation for Linked Data (JSON-LD) format, which provides us with a formal format of the messages transmitted between the components of the in-vehicle system. The resulting ontology is used in the persistence layer of the in-vehicle system we are developing.